Potential of spent coffee grounds for biodiesel production and other applications - Nídia S. Caetano (2013)
This work studied the extraction of lipids from spent coffee grounds (SCG) and the possibility of using the extracted lipids for biodiesel production. Thus, the SCG were first characterized, in particular for their carbon/nitrogen ratio (C/N 8) and higher heating value (HHV = 19.0 MJ/kg). These results show that besides its common use as fertilizer rich in nitrogen, SCG can be used as solid fuel. Concerning the lipids extraction, the best results were obtained using pure hexane and a 50:50 (vol/vol) mixture of hexane and isopropanol and yielded about 6 % (vol/dwt), being higher (about the double) when dry SCG was used instead of wet SCG (with a moisture content of about 66 %, vol/wt). The use of ultrasounds had no significant effect on the extracted lipids. Regarding the lipids characterization, results have shown an acid value in the range of 3.9-12.5 mg KOH/g, a density at 15 ºC in the range of 912-934 kg/m3 , a viscosity at 40 ºC in the range of 14.9-44.0 mm2 /s, an iodine number in the range of 47.6-70.5 g iodine/100 g, and a HHV in the range of 35.4-39.9 MJ/kg, which are negatively influenced by the lipids water content and by the solvents used for the extraction. Due to the relatively high free fatty acid content of the extracted lipids, their conversion into biodiesel was done in a two steps process: an esterification of the free fatty acid followed by a transesterification of triglycerides. The characterization of biodiesel revealed an iodine number of about 70.0 g iodine/100 g lipids, an acid value of about 1.8 mg KOH/g lipid and an ester content of about 86 % (determined by GC analysis). Although these values are not within the NP EN 14214:2009 standard of biodiesel quality, there is the potential for using lipids from SCG for biodiesel production if they are blended with lipids from other sources in order to meet the standard requirements.